Pengaruh Variasi Sambungan pada Crash Box Multi Segmen terhadap Kemampuan Penyerapan Energi dengan Uji Quasi Static - Halman, Halman; Choiron, Moch. Agus; Darmadi, Djarot B. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Along with the elevating number of cars, accidents due to car crashes are increasing. Therefore, technology is needed to reduce the occurrence of the driversâ€™ injuries. Crash box is one of the potential passive safety technology which is widely observed today. Crash box is installed between bumper and chassis, aims to reduce the cassualties when the car crashes. In this article, crash box research was conducted by real experimental method through quasi-static test to evaluate the energy absorption capability of circular-shaped multi-segment crash box. Crash box material was made from aluminum A6063. The connection on each segment is a chamfer with 45o angle. The connections between segments 1 and 2 were varied with 3 connection models, those are 1/4, 1/3 and 1/2 of the total length, i.e.120 mm. The results of the study showed that, the highest energy absorption obtained from the crash box with connection of 1/2 and the energy absorption is 5249.726 J. Crash box type of 1/4 and 1/3 exhibit energy absorption of 3886.238 J and 3106.027 J respectively. Generally, the deformation pattern on the crash box is mixed-mode (axisymmetric-diamond).Â